Towards a German labor market ontology : challenges and applications - Dörpinghaus, Jens [Verfasser]; Binnewitt, Johanna [Verfasser]; Hein, Kristine [Verfasser]; Krüger, Kai [Verfasser] (My University, 2023)
„The labor market is an area with diverse data structures and multiple applications, such as matching job seekers with the right training or job. For this reason, the multilingual classification of European Skills, Competences, Qualifications and Occupations (ESCO) is a good example of the central role of ontologies in this area. However, ESCO cannot provide all the details of local labor market needs and does not provide links to other hierarchies of competences. For example, other taxonomies of occupations and skills are widely used in German-speaking countries, but they are not in a state where they are easily accessible for interoperability and reasoning. In this paper, we present a first version of a German Labor Market Ontology (GLMO) that uses ESCO as a top-level ontology for the target domain. This makes it highly interoperable and comparable to existing ontologies by providing details for the regional structures in German-speaking countries. In addition, we present a detailed evaluation of the provided data and applications, as well as an extensive discussion of future work.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; 370; 330; Arbeitsmarkt; Arbeitsmarktforschung; Datenanalyse; Berufsklassifikation; ESCO